(untitled) (The Voz a Vos Bulletin, 2022)
This paper is about some fundamental aspects of the art of puppetry: Body, object, and dramaturgy, which require some special dispositions from the actor when interpreting or passing through the theater of puppets and objects to give life to a show, and finally think about some projections of research and fields of work on puppets and their many possibilities. Reflections inspired by the work carried out by El Taller de Los Cacharros and the Elective of puppets and objects carried out in the Bachelor of Performing Arts of the UAN during the years 2019 and 2020.